PENGARUH PROMOSI DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SOMETHINC MELALUI LOYALITAS KONSUMEN - Putri, Maharani Anisa; Saputro, Edy Purwo (Jurnal Ilmu Manajemen dan Bisnis, 2025)
The purpose of this study is to analyze the effect of promotions and discounts on purchasing decisions of Somethinc products through consumer loyalty. This study was conducted using quantitative methods. Data were obtained through questionnaires containing statements that had been prepared by researchers and distributed to respondents, the questionnaires were distributed. Data analysis was carried out using Smart-PLS software version 3.0. The results showed that promotions did not have a significant effect on consumer loyalty of Somethinc products. However, discounts were shown to have a positive effect on consumer loyalty. Discounts through consumer loyalty have a significant effect on purchasing decisions of Somethinc products.